Fonem Konsonan, Vokal, dan Diftong dalam Bahasa Minangkabau dan Bahasa Korea: Kajian Linguistik Kontrastif - Amri, Ulil; Husna, Lailatul; Kartika Putri, Aprilia; Zubaidah, Zubaidah; Pratiwi, Anne (Universitas Andalas, 2025)
This descriptive-qualitative research is a comparative linguistic study that applies Qualitative-Comparative Analysis (QCA), which compares Minangkabau and Korean languages in the scope of phonology. The data for this research are of the two languages' sound units, phonemes, and words. The data sources were eight informants who were active speakers of the Minangkabau and Korean languages. Data were extracted through digital interviews by applying the listening method and the derivative of the participatory observation method through recording and note-taking techniques. The note-taking technique was conducted through the transcription method, which includes orthographic, phonetic, and phonemic transcriptions that utilize the IPA alphabet as a transcription standardization. This research focuses on finding the natural similarities and differences in the two languages' consonant, vowel, and diphthong phonemes to assist Minangkabau speakers in learning Korean. The study results show that Minangkabau and Korean languages have a series of similarities and differences in vowel, consonant, and diphthong phonemes. The similarities found are that these languages share the same five vowels, three diphthongs, and 10 consonants. The differences are that the two languages construct different distribution patterns and correspondence of consonants. In contrast, in the Minangkabau language, the voiced and voiceless sounds are of two different phonemes, while in Korean, they are of the same phonemes. In addition, there are also differences in the correspondence and distribution of consonants in various positions in the word.